DNA repair genes: alternative transcription and gene expression at the exon level in response to the DNA damaging agent, ionizing radiation. - Helen B Forrester; Jason Li; Daniel Hovan; Alesia N Ivashkevich; Carl N Sprung (PLoS ONE, 2012)
DNA repair is an essential cellular process required to maintain genomic stability. Every cell is subjected to thousands of DNA lesions daily under normal physiological conditions. Ionizing radiation (IR) is a major DNA damaging agent that can be produced by both natural and man-made sources. A common source of radiation exposure is through its use in medical diagnostics or treatments such as for cancer radiotherapy where relatively high doses are received by patients. To understand the detailed DNA repair gene transcription response to high dose IR, gene expression exon array studies have been performed and the response to radiation in two divergent cell types, lymphoblastoid cell lines and primary fibroblasts, has been examined. These exon arrays detect expression levels across the entire gene, and have the advantage of high sensitivity and the ability to identify alternative transcripts. We found a selection of DNA repair genes, including some not previously reported, that are modulated in response to radiation. Detailed dose and time course kinetics of DNA repair transcription was conducted and results have been validated utilizing PCR methods. Alternative transcription products in response to IR were identified in several DNA repair genes including RRM2B and XPC where alternative initiation sites were found. These investigations have advanced the knowledge about the transcriptional response of DNA repair.